2022
DOI: 10.3389/fpsyg.2022.825036
|View full text |Cite
|
Sign up to set email alerts
|

Does It Matter If Students (Dis)like School? Associations Between School Liking, Teacher and School Connectedness, and Exclusionary Discipline

Abstract: School liking is an important factor in student engagement, well-being, and academic achievement, but it is also potentially influenced by factors external to the individual, such as school culture, teacher support, and approaches to discipline. The present study employed a survey methodology to investigate the associations between school liking and disliking, teacher and school connectedness, and experiences of exclusionary discipline from the perspective of students themselves. Participants included 1,002 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Liking school reflects positive experiences, engagement, and a sense of purpose, contributing to intrinsic motivation and developing a positive worldview. These positive school experiences can foster social–emotional competencies ( Graham et al, 2022 ), including empathy and prosocial behaviors, which in turn cultivate Faith in Humanity and the perception of people as inherently valuable and deserving of dignity. Such early experiences lay the groundwork for positive adult outcomes, contributing to overall Flourishing and forming positive beliefs about Humanity.…”
Section: Discussionmentioning
confidence: 99%
“…Liking school reflects positive experiences, engagement, and a sense of purpose, contributing to intrinsic motivation and developing a positive worldview. These positive school experiences can foster social–emotional competencies ( Graham et al, 2022 ), including empathy and prosocial behaviors, which in turn cultivate Faith in Humanity and the perception of people as inherently valuable and deserving of dignity. Such early experiences lay the groundwork for positive adult outcomes, contributing to overall Flourishing and forming positive beliefs about Humanity.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies in positive psychology have demonstrated the importance of studying people's positive emotions and thinking, positive traits and personalities, and positive environments that predictably lead to their happiness, well-being, and life satisfaction (Seligman, 2006). By the definition of school enjoyment, it is assumed that children who truly enjoy school are comfortable with their school life and, in particular, are satisfied with how they spend their time with other people, such as peers, whom they meet at school (Graham et al, 2022). It is also possible that they see their school as a positive social or learning environment that matches their interests, personalities, and values (Graham et al, 2022).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…By the definition of school enjoyment, it is assumed that children who truly enjoy school are comfortable with their school life and, in particular, are satisfied with how they spend their time with other people, such as peers, whom they meet at school (Graham et al, 2022). It is also possible that they see their school as a positive social or learning environment that matches their interests, personalities, and values (Graham et al, 2022). Given the negative association between school enjoyment and mental health and behavioral problems (Cadman et al, 2021), this suggests that the way in which children view school positively or fully engage in such an educational environment may be an indicator of better school adjustment.…”
Section: School Enjoyment Adaptation and Adjustmentmentioning
confidence: 99%
“…Being suspended from school can undermine a student's ability to keep up with school work and thus disrupts a student's ability to take full advantage of their educational opportunities (Tanner-Smith and Wilson, 2013). Additionally, being suspended deprives students of contact with their classmates and negatively affects their attitudes about school and learning, which creates feelings of being disconnected from school (Graham et al, 2022).…”
Section: Introductionmentioning
confidence: 99%